Does gender affect funding success at the peer-to-peer credit markets? Evidence from the largest German lending platform - Nataliya Barasinska; Dorothea Schäfer (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Studies of peer-to-peer lending in the USA find that female borrowers have better chances of getting funds than males. Is differential treatment of borrowers of different sexes a common feature of peer-to-peer lendingmarkets or is it subject to specific businessmodels, ways of fixing loan contracts and even national financial systems? We aim at answering this question by providing evidence on loan procurement at the largest German peer-to-peer lending platform Smava.de. Our results show that gender does not affect individual borrower's chances of funding success on this platform, ceteris paribus. Hence, gender discrimination seems to be a platform-specific phenomenon rather than a common attribute of this innovative form of credit markets.
Keywords: G21; J16; 330; gender; access to credit; peer-to-peer lending